Employee Development and Retention Strategies for Sustainable Organizational Success (Journal of Universal Excellence, 2026)
Research Question (RQ): What is the significance of employee training and development in an organization, and how does employee retention impact the long-term success of the organization?Purpose: The purpose of this article is to present the importance of employee development and retention in an organization.Method: The research is based on theoretical foundations from professional literature.Results: Employee development and retention are crucial for the long-term success of the organization. Employee training increases their productivity, engagement, and satisfaction, which improves the quality of work and reduces turnover. Investment in training is a long-term investment that enhances the company’s competitiveness and enables better adaptability to changes in the industry. An organizational culture that promotes employee development positively impacts their effectiveness and contributes to the company’s greater stability. In this way, employee development enables lasting success, greater innovation, and market stability for the organization.Organization: The research positively impacts the organization as employee development and retention improve the company’s performance and productivity.Society: The impact of the research on society and the environment is also positive, as employee development fosters a greater knowledge base, encourages teamwork, collaboration, and mutual support, contributing to a better organizational climate.Originality: With a quality strategy for employee development and retention, an organization ensures its success, adaptability to market changes, and competitiveness in the business environment.Limitations/Further Research: The research is based on professional literature and one conducted interview. For a more in-depth analysis, it would be beneficial to conduct more interviews in different organizations.
Keywords: employees; development; retention; organization; performance; sustainability; strategy; competitiveness